Cultural aspects of vaginismus therapy: a case series of Arab-Muslim patients. (9th January 2019) - Zgueb, Yosra; Ouali, Uta; Achour, Radhouane; Jomli, Rabaa; Nacef, Fethi
Abstract: Vaginismus in one of the most frequent causes of non-consummation of marriage, and of infertility, in Arab-Muslim societies. Cognitive behavioural therapy (CBT) proved to be effective, but it is important to consider the cultural context of the patient attending CBT for vaginismus. The aim of our study was therefore to draw attention to the belief systems and behaviours linked to female sexuality and couple relationship in the Arab-Muslim culture. We present a series of four patients representative of the local culture and show how treatment strategies were adapted to fit these behaviours and belief systems, as well as environmental factors. We found that excessive closeness of family members, allowing the family to be intrusive and exercising pressure on the couple, a strict education which highly values virginity, transmits fear of 'the male' and fear of sex, and which links sex with pain, were the common denominator of all patients of our case series. We adapted the classical CBT strategies for vaginismus to our cultural context. The educational component was enlarged. Cognitive techniques were used to modify specific traditional beliefs. The integration of the family, and not only of the partner, into the treatment process proved uniquely beneficial for the patients.